Growth patterns and climate-growth relationships of three Helichrysum shrub species along an elevation gradient in the Drakensberg Alpine Centre - Botha, Tamara (My University, 2020)
Mountains are complex environments owing to environmental lapse rates, varying exposures, changing topography and different microclimatic conditions and, as a result, they act as havens for a variety of ecosystems and high biodiversity. Mountain ecosystems are unique as species remain confined to high elevations compared to areas downslope where vegetation communities occupy broader climatic niches and ranges over wider latitudinal belts. Plant species that grow at these locations are adapted to, or are constrained by, a narrow range of environmental conditions and can be used as possible climate proxies in a changing climate. This study investigates the growth patterns of Helichrysum tenuifolium, H. trilineatum and H. witbergense species along an elevation gradient in the Drakensberg Alpine Centre (DAC) to determine whether they respond to inter-annual climate variability and how microhabitats may influence their growth patterns. Patterns of ring widths differ between two Helichrysum species in the alpine thermal belt (H. witbergense and H. trilineatum) and the two species located in the upper-montane thermal belt (H. tenuifolium and H. trilineatum) are evaluated using dendrochronology and AMS radiocarbon dating methods. Data were collected from Kotisephola Pass (± 3 282 to 3 332 m a.s.l.), Sani Pass-upper (± 2 859 to 2 916 m a.s.l.) and Sani Pass-lower (± 2 514 to 2 585 m a.s.l.). Clearly discernable growth rings were identified in all species and ranged from 0.3 mm to 2.4 mm in width. The growth period and age determined using AMS radiocarbon dating confirmed that these three Helichrysum species form annual growth rings. Shrub abundance analyses confirmed that H. witbergense were only found at high elevations, in mostly cool and moist areas on south-facing aspects. In contrast, H. tenuifolium were only observed at the low elevation study site on eastern aspects. H. trilineatum were found at all three study sites and are more abundant on south- and west-facing slopes, except for the Sani Pass-lower study site where they occur only on east-facing aspects. This research confirms that climate, elevation, and aspect all influence their growth patterns and that these species exhibit specific habitat preferences in terms of microhabitats and ecological niches. There were no consistent statistical trends in shrub growth ring chronologies along the elevation gradient, since shrubs in the alpine and sub-alpine thermal belt have complacent growth patterns. Mean annual temperature, mean growing season temperature and monthly total precipitation rainfall and total growing season rainfall were used for the analysis. Correlation analysis indicated that temperatures in summer had positive correlations with shrub growth (previous December and current January and February for all the sites). Precipitation during the growing season had weak negative relationships with the all chronologies. However, high precipitation was associated with low temperature in early growing season, further supporting that temperature is a growth-limiting factor. Multiple regression analyses confirmed that a combination of temperature, rainfall, aspect, and elevation influences Helichrysum shrub growth. The observed shrub growth response to climate variability increases our understanding of the mechanisms underlying current shrub growth patterns, which is required to predict future climate-driven alpine vegetation patterns
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science, School of Geography, Archaeology and Environmental Studies, 2020